Cytotoxic activity extracts of origanum, salvia and rosa on leukemia cells (Eurasian Journal of Ecology, 2016)
The aim of the work was to determine the effects of 50 and 100% ethanol extracts of origanume, salvia, rosa on growth and differentiation of cell line HL60 (HL60G and HL60MF sublines) of human acute myeloid leukemia(AML). Has been found unequally effect phytopreparations against two cell sublines used in this study. The most sensitive to action plant extracts are the cells of subline HL60MF. 50% ethanol extract of rosa showed the mostactive action, induced growth inhibition depending on a dose. At its highest dose (100 μg/ml) extract also induced a cytotoxic effect. Plant extracts did not affect cell differentiation or changed the differentiation effect of calcitriol, the active form of vitamin D. The antiproliferative effect extract of rosa can be associated with DNA damage cells, which leads to stop cells in the synthetic (S) and presynthetic (G1) phase of the cell cycle. Cell treatment with 100 μg/ml extract resulted in the appearance of cells with subdiploid DNA content (sub-G1), indicating the induction of apoptosis.
Keywords: origanum vulgare; salvia officinalis; rosa canina; acute myeloid leukemia; extracts; proliferation; cytotoxity; cell cycle; DNA; apoptosis.